Relaciones asimétricas del grupo social acllacuna, una visión desde la arquitectura - Risco Patiño, Lorenzo (Pontificia Universidad Católica del Perú, 2024)
This research uses asymmetric dependency studies to discuss the sociopolitical context of the acllacuna social group, focusing on explaining what type of social asymmetry was applied to them. To this end, I reexamine the architectural evidence for the acllahuasis, particularly those of Pachacamac and Cuzco, and incorporate the analysis of space and ethnohistorical data. The result of the research shows that cultural practices such as social control and hierarchisation, together with the deployment of Inca government, fostered the development of asymmetric relations of dependency, such as subjugation and coercion. These relationships impacted the performance of the acllacuna and their interaction within the political and economic domains.

Esta investigación aplica teorías de dependencia asimétrica para discutir el contexto sociopolítico del grupo social acllacuna, centrándose en explicar qué tipo de asimetría social se ejercía sobre ellas. Para ello, reexamino las evidencias arquitectónicas de los acllahuasis, particularmente los de Pachacamac y Cuzco, e incorporo el análisis espacial y la información etnohistórica. El resultado de esta investigación muestra que algunas prácticas culturales, como el control social y la jerarquización, junto con el despliegue del gobierno inca, favorecieron el desarrollo de relaciones asimétricas de dependencia, como la sujeción y la coerción. Estas relaciones impactaron en la performance de las acllacuna y en su interacción dentro de las esferas políticas y económicas.
Asymmetrical relations of the acllacuna social group, an architectural viewpoint
Keywords: Acllacuna; Performers; Acllahuasi; Incas; Asymmetrical dependency; Acllacuna; Actrices; Acllahuasi; Incas; Dependencia asimétrica; https://purl.org/pe-repo/ocde/ford#6.01.02